Microfilaria in Kidney Biopsy Presenting with Nephrotic Range Proteinuria: A Case Report - Kavishwar, Vikas; Munde, Shital; Murthy, Anuradha; Barodawala, Shaikhali (Annals of Pathology and Laboratory Medicine, 2019)
Background: A 59 year old male from the North was referred with Nephrotic Syndrome and heavy proteinuria (8gm) and weakness. Urine examination showed 2-3 pus cells, 4+ protein. Two cores of renal tissue were submitted in buffered formalin and Michel’s transport medium. Objective: The case is presented for its rarity. The discussion will include immunological review and glomerular patterns of injury associated with Microfilaria. Result: The immunofluorescence pattern was negative for IgG, IgM, IgA, C3, C4, C1q, kappa and lambda. The light microscopy revealed 3 glomeruli showing mild increase in mesangial cellularity. Tubules show cloudy change. Interstitium shows focal lymphoid infiltrate. An unusual finding is the presence of segmented microfilaria in glomerular capillaries. Conclusion: Diagnosis of filariasis on kidney biopsy by identifying microfilaria is rare. High index of suspicion is required to diagnose filariasis due to its wide range of clinical presentation and laboratory findings. In the archives of 11O8 renal biopsies over a period of 4 years, this is the first case we came across.